Legal Protection of Health Workers in Emergency Medical Procedures: An Analysis of Legal Certainty in Indonesia and Thailand - Rosnida Rosnida; Akbar, Muhamad Aksan; Muhammad As Ari. AM; Irabiah Irabiah; Yeni Haerani; Patma Sari (Magister Hukum Universitas Semarang, 2026)
This study examines the legal certainty afforded to healthcare workers in performing emergency medical procedures in Indonesia and compares it with the legal protection framework implemented in Thailand. The urgency of this research arises from the increasing criminalization and malpractice claims faced by healthcare workers acting in good faith under high-risk and time-sensitive emergency conditions. Using a normative juridical method that incorporates statutory, conceptual, case, and comparative approaches, this study analyzes Law Number 17 of 2023 on Health in conjunction with Thailand’s Emergency Medical Act and the application of the Good Samaritan principle. The findings reveal that although Indonesian law normatively recognizes legal protection for healthcare workers, its implementation remains weak due to the absence of technical guidelines, inconsistent law enforcement practices, and the limited role of professional medical institutions in the early stages of legal proceedings. In contrast, Thailand provides more effective legal certainty through explicit statutory immunity, integrated institutional support, and a restorative legal approach toward emergency medical practice. The novelty of this study lies in its comparative analysis, demonstrating that Thailand’s qualified immunity model may serve as a normative and institutional reference for strengthening legal protection for healthcare workers in Indonesia, particularly in emergency medical contexts. This study contributes to the development of health law by offering policy-oriented recommendations to enhance legal certainty, professional security, and patient safety.